Synthesis and Characterization of Undoped and Mo Doped Ferrihydrite Nanoparticles - Garg, Pratibha (My University, 2015)
Undoped and Mo doped two lines ferrihydrite nanoparticles are prepared by chemical route. The samples are characterized by x-ray diffractometer, transmission electron microscope, thermo-gravimetric analyzer, differential scanning calorimeter and vibrating sample magnetometer. The average crystallite size and particle size are found to be about 2 nm for both systems. The samples are found to decompose on heating at higher temperatures. The prepared nanoparticles of undoped and Mo doped ferrihydrite are found to be antiferromagnetic at room temperature.
MS, SPMS
Keywords: nanoparticle; SPMS